TRANSLATION EQUIVALENCE AND STRATEGIES IN "LAUT BERCERITA (THE SEA SPEAKS HIS NAME)" NOVEL BY LEILA S. CHUDORI - Melliana; Nurul Fitriani; Yoga Pratama (English Education Department, 2021)
There are many ways that could be done to introduce culture of a country to the international world, one of them is through translation works. This research is conducted by using qualitative approach and content analysis method. The data used in this research are words and phrases found in "Laut Bercerita (The Sea Speaks His Name)" novel by Leila S. Chudori. In this novel, there are many cultural terms, local language from Javanese people, and dictions so that when they are translated to English, they would be interesting because some of the terms, local language and dictions still do not have equivalences in Target Language. In this research, the researcher analyzed 45 data and divided to 2 categories; 19 data in word category, and 26 data in phrase one. The research findings consist of dynamic equivalence, formal equivalence, and equivalence at word levels for translation strategy they are adaptation, communicative translation, semantic translation, descriptive equivalence, idiomatic translation, literal translation, through translation, and transference. The most often strategies used are adaptation, communicative translation, and semantic translation. Through this research, I have knowledge of translation equivalence and how translation strategy being applied to words and phrases.